THEORETICAL FUNDAMENTALS OF HYDRAULIC AND PNEUMATIC AUTOMOBILE CLUTCH CONTROL - Yu. M. Zakharik; O. S. Rukteshel; An. M. Zakharik; Al. M. Zakharik (Наука и техника)
A clutch drive that provides transmission switching and automobile starting has been designed. A mathematical description of hydraulic and pneumatic automobile clutch control has been made. The description permits to study dynamic processes in the drive, which have an influence on the equation quality. Assumptions considered in mathematical description have been justified.